Synergistic combination of valproic acid and oncolytic parvovirus H‐1PV as a potential therapy against cervical and pancreatic carcinomas. Issue 10 (17th September 2013) - Li, Junwei; Bonifati, Serena; Hristov, Georgi; Marttila, Tiina; Valmary‐Degano, Séverine; Stanzel, Sven; Schnölzer, Martina; Mougin, Christiane; Aprahamian, Marc; Grekova, Svitlana P.; Raykov, Zahari; Rommelaere, Jean; et al.
<x xml:space="preserve">Abstract</x> The rat parvovirus H‐1PV has oncolytic and tumour‐suppressive properties potentially exploitable in cancer therapy. This possibility is being explored and results are encouraging, but it is necessary to improve the oncotoxicity of the virus. Here we show that this can be achieved by co‐treating cancer cells with H‐1PV and histone deacetylase inhibitors (HDACIs) such as valproic acid (VPA). We demonstrate that these agents act synergistically to kill a range of human cervical carcinoma and pancreatic carcinoma cell lines by inducing oxidative stress, DNA damage and apoptosis. Strikingly, in rat and mouse xenograft models, H‐1PV/VPA co‐treatment strongly inhibits tumour growth promoting complete tumour remission in all co‐treated animals. At the molecular level, we found acetylation of the parvovirus nonstructural protein NS1 at residues K85 and K257 to modulate NS1‐mediated transcription and cytotoxicity, both of which are enhanced by VPA treatment. These results warrant clinical evaluation of H‐1PV/VPA co‐treatment against cervical and pancreatic ductal carcinomas.